Molecular characterization of mecA gene in Methicillin-Resistant Staphylococcus aureus - Salman Hamim, Saad (University of Thi-Qar Journal of Science, 2016)
objectives: It is clear now that methicillin-resistant Staphylococcus aureus (MRSA) strains considered as one of the most bacteria responsible for different diseases among humans and animals. The present study aimed todetect the molecular profile of methicillin-resistant S. aureus isolated from skin abscess patients in Nassyriah City, Southern Iraq.Methods: During the period of from June 2014 to February 2015, 120 S. aureus were isolated from abscess patient in two governmental hospitals, and subjected to conventional Polymerase Chain Reaction which used for the amplification of 310 bp mecA gene. Three PCR products of mecA were named primarily (THQR1, THQR2, and THQR3) were selected and subjected to partial DNA sequencing for the mecA gene to follow up their possible relationship between these local isolates and what recorded globally in Genbank. Results: Only 64 S. aureus isolates were diagnosed phenotypically as MRSA (53.33%), and 88/120 (73.33%) of S. aureus were positive for the targeted gene. The Three PCR products of mecA were registered in Genbank under the official accession numbers of (KY468502, KY468503 and KY468504, respectively). The constructed phylogenetic tree showed that S. aureus KY468502 and KY468504 were highly relative to each other in comparison with S. aureus KY468503 that revealed a close relatedness to S. aureus TN/CN/1/12, mecA gene beta-lactam, and mecA gene isolated in USA.conclusions: The present study results confirmed the importance of mecA gene in MRSA detection and highlighted the increasing manner of its prevalence in Iraq, furthermore, the importance of molecular techniques as an epidemiological tool.